Rose Propagation by Tissue Culture - ANOUSACKA, Phonekeo; THAMMAVONG, Khamko; SITTHIVOHANE, Insavai; CHASENGSONG , Kisong; DAOVONGDEUAN , Siphan (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This experiment was tested rose shoots by benzyl adenine (BA) in different concentrations on agarose culture media in in vitro condition. This research aims to investigate the influence of the best concentration of BA on rose tissue culture in the laboratory of the Faculty of Agriculture and Forestry Resource, Souphanouvong University. The research used a Completely Randomized Design (CRD). After culture 4 weeks it was found that T1 with no BA contains (0mg/l) indicated the Number of leaves, shoot elongation, number of the shoot as 7.28 leaves, 1.15 cm, and 1.14 shoots respectively. The T2 BA contains 1 mg/l showed that 11.28 leaves, 1.64 cm shoots elongation, 1.14 shoots. The T3 with BA contains 2 mg/l resulted in the 10.85 number of leaves, 1.31 cm shoot elongation, 3.00. The T4 contains BA 3 mg/l promoted to the 11.57 number of leaves, 1.32 shoots elongation, 2.14 shoots. The T5 contains 4 mg/l showed 13.14 number of leaves leaf, 1.40 cm shoot elongation, 3.57 number of shoots, Finally, T6 BA contains 5 mg/l to 14.00 Number of leaves, 1.15 cm shoot elongation, 3.42 shoots. This investigation indicated that each contains of BA concentracents effected on the number of leaves, shoot elongation and number of shoots at P-Value 0.002 < 0.01, P-Value 0.02 < 0.05, P-Value 0.00 < 0.01 repestively. Although T6 had a higher number of indicators than others treatments, it will be used to promote the tissue proliferation of roses.